An investigation into the effects of healthy adult ageing on everyday multitasking and the cognitive correlates that contribute to enhanced performance - Pickersgill, Mhairi (The University of Edinburgh, 2013)
Multitasking is an extremely important skill and one that is ubiquitous to success in everyday life. Patients with frontal lobe damage have shown impairments in their ability to multitask, despite performing normally on traditional neuropsychological tests of executive function. The frontal lobes are associated with natural age-related decline which, as a result, may cause impairment in the multitasking ability of older adults. This study investigates the effects of healthy adult ageing on multitasking by comparing the age-related performance of older adults (aged 60-80) with younger adults (aged 18-40). The supportive cognitive constructs underlying enhanced multitasking performance and the age-related trajectory of these constructs in terms of their relative influence are also investigated in this study. Participants were tested on a measure of multitasking involving 4 subtasks which were to be attempted within a 10 minute period, with the overall aim being to score as many points as possible across all 4 tasks; 20 young adults and 20 old adults were tested. Results showed a significant difference (p<0.05) in multitasking performance between young and old age groups, with older adults performing significantly poorer than young. Retrospective and prospective memory significantly correlated with multitasking performance in both young and old age groups, but elicited stronger correlations and explained a larger proportion of the variance in younger adults performance than old. In healthy adult ageing this decline in the supportive cognitive constructs of retrospective and prospective memory meant an increased dependency on factors such as intelligence and general cognitive ability in order to successfully multitask. These age-related changes in the cognitive correlates supporting multitasking performance and the emerging importance of intelligence and cognitive ability to the sustainability of performance in old age has important implications for future research regarding multitasking and ageing.
Keywords: multitasking; ageing